« Humaniser » les soins dans l’épidémie d’Ebola ? Les tensions dans la gestion du care et de la biosécurité dans le suivi des sujets contacts au Sénégal - Alice Desclaux; Khoudia Sow (Anthropologie & Santé)
Anthropologists were called by the WHO to "humanize" the response to the Ebola outbreak. Yet, frontline actors had developed practices that shared this goal; this article documents these agents’ community surveillance practices. Institutions involved in the Senegalese outbreak relied on volunteers from the Senegalese Red Cross to conduct a 21-day follow-up of 74 contacts "at risk" of being contaminated and transmitting the virus. In-depth interviews with these officers carried out as part of an ethnographic research project about the outbreak show their multiple care practices, which can conflict with biosafety measures in contact follow-up, reflecting an evolving conflict of logics during the crisis. This analysis contributes to the debate about the coercive nature of public health measures in the response to emerging epidemics and on tensions between control and care, and calls for the inclusion of frontline actors’ experience to define surveillance modalities.